SUGAR LEVELS AND PROTEIN LEVELS OF URINE SAMPLES DECREASED DUE TO THE DELAY OF EXAMINATION OF 1 HOUR AND 2 HOURS: KADAR GULA DAN KADAR PROTEIN SAMPEL URIN MENURUN KARENA TERTUNDANYA PEMERIKSAAN 1 JAM 2 JAM - vetra susanto; Rita Permata Sari; Endang Suriani; Sri Suciana (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2023)
The sugar levels and protein levels in a urine sample may change over time after sampling. Such delays can affect the stability or degradation of components in the urine, including sugar and protein. Several studies have been conducted concerning that delay such as the difference in the length of time of the delay. But the information that the delay affects the sugar content and protein content of the sample, has not been studied much. The purpose of the study was to analyze the sugar levels and protein levels of urine samples that experienced delayed examination. This study was a laboratory study, with the sample being urine. Because of this, a clearance ethics test was carried out. Chemical Analysis of urine is the measurement of chemical components in urine, namely sugar (glucose), protein, uric acid, ketones, bilirubin, nitrite, and urine pH. Chemical analysis can help in the diagnosis of certain diseases or conditions, such as diabetes, kidney disease, urinary tract infections, or liver disorders. The result was that urine levels and protein levels dropped after a delay in examination for 1 hour and 2 hours. Postponement of the examination lowers the sugar level and protein content of the urine sample. By understanding the changes in sugar and protein levels that can occur during delayed urine examinations, healthcare practitioners can make more informed decisions in the diagnosis and management of patients.